When Insurers Go Bust : An Economic Analysis of the Role and Design of Prudential Regulation - Plantin, Guillaume (Book collections on Project MUSE., 2007)
In the 1990s, large insurance companies failed in virtually every major market, prompting a fierce and ongoing debate about how to better protect policyholders. Drawing lessons from the failures of four insurance companies, When Insurers Go Bust dramatically advances this debate by arguing that the current approach to insurance regulation should be replaced with mechanisms that replicate the governance of non-financial firms. Rather than immediately addressing the minutiae of supervision, Guillaume Plantin and Jean-Charles Rochet first identify a fundamental economic rationale for supervising t.